Penerapan Model Pembelajaran Kooperatif Tipe Examples Non Examples dalam Meningkatkan Hasil Belajar Fisika Pada Peserta Didik Kelas XII.IPA1 SMAN 1 Kinali - Deti S.Pd (STKIP Pesisir Selatan, 2016)
AbstrakTeachers are required to understand and apply a variety of learning methods, so that students are more active in the learning process. One method appropriate learning in physics learning is cooperative learning model examples of non examples. The problems to be examined in this study is: Does the use of cooperative learning model Non Examples Examples can improve learning outcomes Physics XII.IPA1 grade students of SMAN 1 Kinali ?. The purpose of this action research was to determine the increase in Physics learning outcomes through the use of cooperative learning model Examples Non-Examples learners XII.IPA1 SMAN 1 Kinali. This study uses classroom action research as much as two rounds. Each round consists of four phases: planning, implementation, observation and reflection. Goal of this research is XII.IPA1 grade students of SMAN 1 Kinali. The data obtained are quantitative and qualitative data. From the results of cooperative learning model examples of non examples of each cycle, the first cycle (65.00%), the second cycle (82.50%). The conclusion of this study is cooperative learning model Examples Non-Examples have a positive effect, which can increase learning outcomes of students shown by the average response of students stating that learners interested and are interested in cooperative learning model Examples NonExamples so that they be motivated to learn.Keywords: Physics, cooperative learning model Examples Non-Examples